Rainwater Measuring Algorithm in O(1) Time Complexity - Vaishnavi Somvanshi; Vaishnavi Pawar; Sharada Patil (International Journal of Data Structure Studies, 2024)
The Rain Terraces Time Complexity Data Structure Algorithm (RTTCDSA) introduces a novel method for managing temporal data efficiently, inspired by the natural flow of rainwater on terraced landscapes. This study presents the conceptual framework and implementation details of RTTCDSA, which leverages principles of temporal dynamics and landscape morphology to organize and query temporal data with optimal time complexity. RTTCDSA employs a hierarchical structure akin to terraced landscapes, facilitating rapid traversal and retrieval operations over temporal data sets. By simulating the temporal flow of rainwater, RTTCDSA optimizes data access patterns, resulting in superior time complexity performance. Experimental validation demonstrates the effectiveness of RTTCDSA across diverse temporal data management tasks, including time series analysis, event sequencing, and historical data reconstruction. This study provides a concise overview of RTTCDSA, highlighting its potential to enhance scalability and efficiency in temporal data management, thus fostering advancements in temporal data analysis and applications.
Keywords: Brust force algorithm; The Rain Terraces Time Complexity Data Structure Algorithm (RTTCDSA); and analysis; data structure; dynamic algorithm; elevation map